Cardiac Tamponade Due to Liver Amebiasis Rupture - Birry Karim; Afifah Is; Ikhwan Rinaldi; Dono Antono; Cleopas Martin Rumende; Andri Sanityoso Sulaiman (The Indonesian Society for Digestive Endoscopy, 2010)
Amebiasis is common cases in Asia, Africa, and South Africa. Liver amebiasis has become a serious problem worldwide especially in health and social aspect. The protozoa named Entamoeba histolytica was easily found in area with poor sanitation, low socioeconomic status, and poor nutrition status. The incidence of amebiasis in several hospitals in Indonesia is 5-15% per year. Epidemiological observation showed the comparison of incidence among male and female population and it was approximately 3 : 1 until 22 : 1 with male predominance. The potential age suffered from amebiasis is around 20 - 50 years old. The route of infection spread to oral-fecal and oral-anal-fecal. The most common complication is abscess rupture (5-15.6%). Rupture may be located in pleural cavity, pericardial cavity, lung, bowel, intraperitoneal, and skin. Rupture of liver amebias spread to pleural and pericardial cavity is a rare case and frequently under reported. This case report illustrates a 40-year-old male with cardiac tamponade due to rupture of liver amebiasis. Patient’s was admitted with chief complaint of shortness of breath, positive Beck’s triad, hepatomegaly, pleural effusion, liver abscess on sonography and swinging of heart on echocardiography. This patient was treated with metronidazole as a drug of choice, and pericardiocentesis for the cardiac tamponade.Keywords: cardiac tamponade, Entamoeba histolytica, oral-anal-fecal, metronidazole, pericardiocentesis